THE DEGREE OF INVOLVEMENT OF THE LEVEL OF CIRCULATING IMMUNE COMPLEXES AND RED BLOOD CELLS IN THE PATHOGENESIS OF COMMUNITY-ACQUIRED PNEUMONIA - Berezniakov, V.I.; Korzh, A.N.; Pavlov, S.B.; Yeroshenko, G.A.; Shevchenko, K.V.; Vatsenko, A.V.; Ulanovska-Tsyba, N.A. (World of Medicine and Biology, 2022)
The paper presents the findings of the study of the degree of involvement of the level of circulating immune complexes and red blood cells in the pathogenesis of community-acquired pneumonia. Marked disorders in immunological indices of the severity degree of the disease in patients with community-acquired pneumonia have been established, which must be taken into account when diagnosing the disease: elevated circulating immune complexes level in the blood serum of patients and an increase in the total circulating immune complexes level, mainly due to an increase in the most toxigenic small- (
Keywords: community-acquired pneumonia; circulating immune complexes; erythrocytes; haemoglobin